2022
DOI: 10.1002/ijch.202200090
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistive Single‐Molecule Junctions: the Role of the Spinterface and the CISS Effect

Abstract: This review is an effort in putting together the latest results about room‐temperature magnetoresistive (MR) effects in nanoscale/single‐molecule electronic devices consisting of one (few) molecule(s) placed in electrical contact between two nanoscale electrodes. Molecules represent powerful building blocks for developing state‐of‐the‐art MR devices, as they bring long spin relaxation timescales, low cost and high tunability of their electrical and magnetic properties via chemical modifications. The capability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…[ 25 ] The role of the spinterface has also been studied in the frame of the CISS effect in single‐molecule junctions. [ 26,27 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] The role of the spinterface has also been studied in the frame of the CISS effect in single‐molecule junctions. [ 26,27 ]…”
Section: Introductionmentioning
confidence: 99%
“…[25] The role of the spinterface has also been studied in the frame of the CISS effect in single-molecule junctions. [26,27] To the best of our knowledge, the coupling of chiral molecules, CISS effect, and spintronic devices has mainly been exploited in spin valves and Hall sensors. Magnetoresistance have been measured in four probe devices and in molecule/ferromagnet bilayer systems for various organic systems of opposite handedness, such as DNA, superhelical polyaniline microfibers, oligopeptides, supramolecular polymers, and metal-organic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies do not unequivocally show that the spin-filtering is a single molecule process, they do show that spin-filtering can occur through a few molecules, at most. In other work, Diez-Perez and co-workers used STM-break junction experiments to study spin-filtered electron currents through peptides and found that the sign of the spin polarization changes with the chirality of the molecules. , While these studies demonstrate that the spin-filtered currents manifest for single molecules, the interpretation of the data require that one include some spin-filtering from the ferromagnet-molecule interface.…”
Section: General Trends and Structure–property Relationshipsmentioning
confidence: 99%
“…The chirality-induced spin-selectivity (CISS) effect is considered as a general name for a group of effects, characterized by a different electronic response to an external stimulus in the presence of chiral molecules. The two central manifestations of the CISS effect are observed in photoemission experiments and transport experiments. In photoemission experiments, electrons are photoexcited to leave a metal covered by chiral molecules, and the rate of emission depends on the polarization of the illumination (or more precisely on the relation between the polarization of the light and the chirality of the molecular layer). In transport experiments, current is passed through a metal-chiral molecule-ferromagnet (FM) junction, and the current is different depending on the FM being magnetized parallel or antiparallel to the molecular chiral axis (which is typically also the direction of current flow).…”
Section: General Formulation Of Ciss Polarizationmentioning
confidence: 99%